Analysis of Robusta Coffee Production Forecasting and Financial Feasibility of Home Industry Spice Coffee Businesses in Sukarame District, Bandar Lampung City - Chintia Agrefina Brilian; Warastra Nur Annisa; Ahmad Fitri; Maria Magdalena Sinaga (Jurnal Teknologi Agro-Industri, 2025)
Forecasting analysis was used to predict the availability of Robusta coffee in Lampung as a basis for developing innovative coffee-based products, such as spiced coffee. Furthermore, financial analysis was conducted to assess the feasibility of processing spiced coffee as a regional flagship product. This research was conducted through a literature study from various sources, and data analysis was performed using POM-QM for Windows Version 3 software. The results of the study show that Robusta coffee production in Lampung tends to be stable from 2022 to 2026. In 2026, Robusta coffee production in Lampung will reach 116,272 tons. Financial analysis shows feasibility with an NPV of IDR 167,473,835.26, IRR of 222%, Net B/C of 2.76, Gross B/C of 1.26, and a PBP of 1 year. The investment can be recouped in 2 years, making the spice coffee home industry a viable venture to develop.